Punishment Asset Forfeiture for Corruptor In Perspective of Indonesian Community Justice - Yaris Adhial Fajrin; Ach. faisol triwijaya (Fiat Justisia: Jurnal Ilmu Hukum, 2019)
This study discusses the prospect of criminal asset forfeiture in the Corruption criminal act as a staple criminal. The research is based on the fact that the state's financial loss recovery due to corruption crimes is not achieved, whereas the purpose of law enforcement corruption is aimed at restoring the state's financial losses. But these objectives are not manifested through proper pipetting to accomplish that goal. The purpose of this research is to assess the prospect of asset deprivation as a staple criminal in the framework of national criminal law reform. The methods used in this study used normative research methods with a conceptual approach as a breakthrough problem occurred. This research gain results when criminal asset forfeiture is placed as principal criminal; it will realise the goal of state financial recovery due to corruption crimes and will be aligned with community justice.